Desarrollo de estrategia de precios basado en el análisis de planeamiento de demanda y comercial en el rubro automotriz - Rodriguez Rios, Fabiola Marianella (2020)
The purpose of this project is to support the hypothesis that the redesign of the main processes involved in commercial transactions of luxury automobiles will allow the total sale of an unusual high stock through automotive market analysis and commercial management tools. The main objective is to sell the entire stock in three months. In the first part, the analysis focuses on the automotive market highlights and its changes in 2018. Moreover it includes internal analysis of the most important processes and structure of Euromotors, the importer company. As a result, it is discovered that the problem is the combination of bad market spectrum for selling high volumes of luxury vehicles and a poor purchasing strategy in the planning area. In the second part, possible solutions are presented and the pertinent study is carried out in order to choose the most appropriate ones. These are based on a better pricing structure supported by a powerful commercial campaign. Finally, the integral solution is developed by setting the investment amount and opportunity cost. As a result, the investment amount turns out to be US$ 255,280 in order to achieve the main objective. The income when carrying out the project turns out to be US$ 2, 059,258 with an ROI of 480%.